Prescribing Prism for Aniseikonia: A Case Report and Review. - Kundart, James (Optometry & Visual Performance, 2020)
Subjective: A 62-year-old male first reported to our clinic with a chief concern of a larger image size in the left eye. There was a history of blunt trauma to the right nasal canthus almost 40 years previously. The patient reported that he was generally healthy with a history of hay fever or the use of nasal spray. Objective: Refraction showed low compound hyperopic astigmatism with absolute presbyopia. Over five visits in a three-year period, 12? esophoria was measured at far using associated methods. Without prismatic correction, a 6% image size difference OS was found. Optical coherence tomography (OCT) of the anterior segment showed central corneal thickness of 524 microns OD and OS, and OCT of the macula showed increased central thickness OS. Additional case history revealed the use of a steroid nasal spray in the left nostril only for the past two decades. His highest recorded blood pressure was 155/85. Intraocular pressure was measured at 11 mm Hg OD and 24 mm Hg OS. Assessment: The patient was diagnosed with divergence insufficiency, possibly secondary to abducens (CN VI) partial paresis, ocular hypertension OS, and central serous retinopathy OS secondary to systemic hypertension. Plan: The patient was prescribed 6? BO prism OD and OS (for a total of 12? BO). This prescription eliminated his aniseikonia without the need for a size lens. He was advised to discontinue the nasal spray and was prescribed latanoprost 0.005% QHS OS. The patient was advised that controlling hypertension might resolve the central serous retinopathy and aniseikonia and might change his need for prism.